Scanning Density Gradient Isoelectric Focusing of Staphylococcus aureus Enterotoxins B and C(1) - Yotis, William W. (1974)
Purified Staphylococcus aureus enterotoxins B and C(1), the causative agents of staphylococcal food poisoning, were resolved into several components by scanning isoelectric focusing in sucrose density gradients in the absence and presence of 6 M urea and 5 mM dithiothreitol. The observed heterogeneity persisted in the denaturing medium, which suggests that the primary structure of protein enterotoxins B and C(1) may be partly responsible for the isoelectric point differences of the various forms. To our knowledge, the scanning isoelectric focusing patterns of staphylococcal enterotoxins B and C(1) are reported for the first time.